Categorically complex: A latent class analysis of public perceptions of police militarization. (September 2018) - Fox, Bryanna; Moule, Richard K.; Parry, Megan M.
Abstract: Purpose: The events in Ferguson, MO in 2014 renewed national attention to the issue of militarization of law enforcement. Despite scrutiny from policymakers and community stakeholders, little is known regarding the public's opinion on police militarization (PM), or the factors shaping these views. This problem is magnified because individuals may support or oppose PM for a variety of reasons, but the characteristics of these supporters and opposers is currently unknown. This study aims to examine the distinct types of individuals who support or oppose PM, and the normative, instrumental, and demographic factors that distinguish within- and between-groups of supporters and opposers of PM. Methods: Using a national sample of 702 American adults, a series of Latent Class Analyses were conducted using data on normative and instrumental characteristics of individuals who support and oppose PM. Results: Results indicate three unique sub-types of PM supporters and two unique sub-types of opposers, and each contain a distinct combination of normative and instrumental concerns and beliefs. Normative orientations distinguish between overall PM supporters and opposers. Within-group variations appear to be a function of additional characteristics. Conclusions: These findings demonstrate the complexity of the public sentiment toward this controversial topic in contemporary American policing. Highlights: Over half (58%) of the sampled Americans did not support police militarization (PM). Supporters of PM showed substantially higher levels of perceived legitimacy and trust in the police versus those who did not support the practice. Normative, instrumental, and demographic features are not uniform within groups of PM supporters and opposers. Latent Class Analyses indicate three unique sub-types of supporters and two unique sub-types of opposers exist within the data. Practitioners should be cognizant of the role normative beliefs play in garnering support for militarization and other police practices.